Molecular Systematics Of Subterranean Termites Coptotermes Spp., Microsatellite Development And Population Genetics Of Coptotermes Gestroi (Wasmann) (Blattodea: Rhinotermitidae) - Yeap , Beng Keok (2010)

(untitled)
This dissertation focused on the systematics and phylogenetic relationships of the subterranean termites (genus Coptotermes), and population genetics of Coptotermes gestroi (Wasmann). The phylogenetic relationships of 14 putative Coptotermes spp. [Coptotermes acinaciformis Froggatt, Coptotermes cochlearus Xia & He, Coptotermes curvignathus Holmgren, Coptotermes dimorphus Xia & He, Coptotermes frenchi Hill, Coptotermes formosanus Shiraki, Coptotermes gestroi, Coptotermes guangzhouensis Ping, Coptotermes heimi (Wasmann), Coptotermes kalshoveni Kemner, Coptotermes lacteus (Froggatt), Coptotermes sepangensis Krishna, Coptotermes travians (Haviland), and Coptotermes vastator Light] were determined using mitochondrial DNA sequences (12S, 16S, and COII genes). Available sequences from the Genbank for these species were also included in the analyses. Maximum parsimony and maximum likelihood of the combined nucleotide matrices of the 12S, 16S, and COII genes resulted in two major clades with six subclades: I (C. acinaciformis), II (C. lacteus and C. frenchi), III (C. curvignathus), IV (C. kalshoveni, C. sepangensis, and C. travians), V (C. gestroi, C. heimi, and C. vastator), and VI (C. formosanus, C. cochlearus, C. dimorphus, and C. guangzhouensis).